EFEKTIVITAS TEPUNG TERIPANG PASIR (Holothuria scabra) TERHADAP MASKULINISASI IKAN CUPANG (Betta splendens) - Yustina '; Arnentis '; Dian Ariani (Biogenesis, 2012)
The research was to knowing effectivenes of sand Sea-cucumber (Holothuria scabra) flour to maskulinization fish of cupang (Betta splendens) are held in Desember 2011 until February 2012. The research method used experiment method with design of experiment are complete random device (RAL). The research consits of three treatment are treatmen of B (dose of sea-cucumber 10 mg/l), treatment of C (dose of sea-cucumber 20 mg/l), treatment of D (dose of sea-cucumber 30 mg/l), while control consist of treatment of A (dose of sea-cucumber 0 mg/l) and treatment of E (17α-metiltestosteron dose 10 mg/l) with 3 times restating. Treatment of sand sea-cucumber flour are given for larva fish of cupang wich old age 4 day with soaking during 6 hour. Observed parameter are the male sex ratio, pass of life and environmental factor are the temperature, pH, Oxygen content dissolved and carbondioxyde content dissolved, while data are analyzed with ANAVA resulth and further rested by LSD at 5% level of confidence. The results of experiment showed that teh highest percentage of male fish at treatment of D (dose 30 mg/l) are 66,66% and the lowets of treatment of A (dose 0 mg/l) are 39,77%. From these results it can be concluded that the sand sea-cucumber flour hae given to test larva effectiv to maskulinization fish of cupang female become male.Keyword: Betta splendens, Sand sea-cucunber flour, 17α-metiltestosteron and maskulinization